SOLITON TRAPPED IN 2X2 DIRECTIONAL FIBER COUPLER - Dedi Irawan; Saktioto '; H.M. Hairi; Jalil Ali (Komunikasi Fisika Indonesia, 2014)
The study of soliton trapped in 2X2 directional fiber coupler is reported. By introducing an optical signal with high intensity into two cores of directional fiber coupler will create the soliton pulse in that coupling region. Soliton can carry the data in an extended distance without distortion with high-speed, so that it is promising an ideal communication system in a long distance. In its propagation, the loss was still appears. It is caused by the trapping of soliton pulses at the coupling region so that the collision take placed.The collision of two coupled solitons was determined from the Non-linear Schroodinger Equation (NLSE) based on the Coupling Mode Theory (CMT). The distance of collision can be reduced by decreasing the separation of the two soliton pulses. Another way can be done by choosing a value of medium misalignment saturation H. for the value of H=0.1, it can be seen clearly that length of pulse propagating more broaden. The relationship between the amplitude and width of a soliton is also investigated. It is found that increasing the width, the amplitude also increases. However, the knowledge of collision between two trapped solitonsis important and promises a good application forthe optical switching.